Періодичні розв’язки систем диференціально-функціональних рівнянь із лінійними відхиленнями аргументу та їх властивості - Денисенко, Н.Л. (Нелінійні коливання, 2009)
Установлены достаточные условия существования периодических решений систем линейных
и нелинейных дифференциально-функциональных уравнений с линейными отклонениями аргумента и исследованы их свойства. Sufficient conditions for existence of periodic solutions of systems of linear and nonlinear differentialfunctional equations with linear deviations of the argument have been established and their properties
have been studied.